Exploring Causes Behind Ineffectiveness of In-service English Language Teacher Training in Nepal: A Causal Layered Analysis - Ghimire, Ramesh Prasad (NELTA Bagmati Journal, 2022)
Teacher professional development has remained the focus of the government of Nepal since the late 1940s. Various initiatives have been taken by the government for the professional development of the teachers. However, the transfer rate of the training skills to the classroom is found to be very low. Despite the continuous involvement of the teachers in in-service training opportunities there is the dominance of teacher-centred activities in the classroom and learners’ language achievement has remained unsatisfactory. The aim of this study was to explore the causes behind the ineffectiveness of the in-service English language teacher training in Nepal. The main method used was the Causal Layered Analysis (CLA) (Inayatullah, 2004). Systematic analysis of the existing literature revealed that ineffectiveness of the training is caused by various factors which are operating at four different levels, viz. litany, systems, worldviews and myths and metaphors. However, the causes at system level are more serious and hence need early attention for reform initiatives in the future. At the system level there are teacher-related, training-related and school-related factors playing an unsupportive role for the effectiveness of the training. Based on these findings, some recommendations for future actions have also been made.